WARRANTY RESULTING FROM EARTHQUAKE AND SUPERVISOR LIABILITY IN THE QUASI-JUDICIAL PROCEDURE MIRROR IN IRAN - Bahman Moradifar, Hosein Sheykholmoluk (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Liability arising from earthquake and responsibility of construction observers in the field of quasi-judicial precedent. This is a general rule that in natural disasters occurring throughout the world some incidents with the same effect must amount to the same consequences. This approach cannot be seen in practice because some natural disasters with the same intensity cause unequal damages. In Kermanshah province, statistics show that there are some natural incidents with the same intensity the outcome has been different [1]and this indicates that governments with long-term planning and standardization have been successful in decreasing damages. In the field of law, lawyers have paid attention to The Liability of government in these cases a type of civil liability that due to progress in science and technology is far from the traditional concept of civil liability and is regarded as evolutionary responsibility which is related to Philosophy and sociology. In this research we are going to answer this question: 1) is it logical that a natural disaster happening centuries ago with a huge amount of damages should amount to the same amount of damages?